Girls of Riyadh: Issues of Translation and Ideology - Al Jerjawi, Solafa (2011)
A Master of Arts thesis in Translation and Interpreting by Solafa Al Jerjawi entitled, "Girls of Riyadh: Issues of Translation and Ideology," submitted in June 2011. Available are both hard and soft copies of the thesis.